Genetic footprints of adaptive divergence in the bracovirus of Cotesia sesamiae identified by targeted resequencing. Issue 8 (23rd April 2018) - Gauthier, Jérémy; Gayral, Philippe; Le Ru, Bruno Pierre; Jancek, Séverine; Dupas, Stéphane; Kaiser, Laure; Gyapay, Gabor; Herniou, Elisabeth A.
Abstract: The African parasitoid wasp Cotesia sesamiae is a generalist species structured in locally adapted populations showing differences in host range. The recent discovery of Cotesia typhae, a specialist, sister species to C. sesamiae, provides a good framework to study the genetic determinants of parasitoid host range. To investigate the genomic bases of divergence between these populations and species, we used a targeted sequencing approach on 24 samples. We targeted the bracovirus genomic region encoding virulence genes involved in the interaction with the lepidopteran hosts of the wasps. High sequencing coverage was obtained for all samples, allowing the study of genetic variation between wasp populations and species. By combining population genetic estimations, such as nucleotide diversity (π), relative differentiation ( F ST ) and absolute divergence ( d xy ), with branch‐site dN/dS measures, we identified six of 98 bracovirus genes showing significant divergence and evidence of positive selection. These genes, belonging to different gene families, are potentially involved in host adaptation and in the specialization process. Fine‐scale analyses of genetic variation also revealed mutations and large deletions in certain genes inducing pseudogenization and loss of function. The image emerging from these results is that adaptation mediated by bracovirus genes happens through selection of particularly adaptive alleles and loss of nonadaptive genes. These results highlight the central role of the bracovirus in the molecular interactions between the wasps and their hosts and in the evolutionary processes of specialization.